HISTORICAL DEVELOPMENT OF INFORMATION CULTURE IN THE EDUCATIONAL PROCESS AND ITS CONTEMPORARY PEDAGOGICAL SIGNIFICANCE - Algozhaeva Nursulu Seitkerimovna; Shakhnoza Irkinovna Sheralieva (Bright Mind Publishing, 2026)
This article examines the historical development of information culture and its contemporary pedagogical significance within the educational process. The study analyzes the main stages of information culture formation in connection with major information revolutions, from the emergence of writing and printing to the development of modern digital technologies. Special attention is given to the role of information and communication technologies in shaping learners’ information culture, media literacy, and critical thinking skills. The paper highlights the pedagogical importance of information culture in developing students’ intellectual potential, independent learning abilities, and responsible use of information in the digital environment. The findings emphasize that integrating historical experience with modern pedagogical approaches contributes to the effective formation of information culture and supports the development of an informed, competent, and socially responsible generation in the context of an information-oriented society.
Keywords: Information culture, educational process, information society, media literacy, digital technologies, pedagogical significance, critical thinking.